(untitled) (Development Service Industry Management, 2023)
The nature protection areas of the Transboundary Biosphere Reserve (TBR) «Roztochchia» on the Ukrainian-Polish border were investigated in the paper, to use them for the development of tourism. In particular, the possibilities and peculiarities of conducting tourist activities in nature conservation areas were determined and the importance of tourism in the structure of the functioning of the cross-border biosphere reserve «Roztochchia» was determined. The existing tourist potential of the TBR was characterized and the objects of the recreational zone of the parks were analyzed to use them in tourism. The international experience of popularizing tourism in nature-protected areas and the possibilities of its implementation in Ukraine were studied, and the prospects for the development of recreational activities within the boundaries of the Roztochchi TBR were outlined. It has been established that the development of the tourism and recreation industry is a priority in the territory of the Roztochchia TBR. In the buffer zones of the reserve, tourist and recreational activities are supported, aimed both at reducing the tourist load on the protected area and at increasing the tourist and recreational attractiveness of the transit zone. The use of the «Roztochchia» TBR for this purpose will contribute to the development of various types of tourism in the region, in particular: ecological, green, agritourism, hiking and bicycle tourism, as well as cultural and educational, etc. The villages of Lelekhivka, Vereshchytsia, Stavky, Verkhutka, Seredniy Horb, Lozyna, Stradch, as well as the town of Ivano-Frankivsk - Romanivka, etc., are promising in this aspect. A correctly planned, functionally regulated, and sufficiently advertised network of tourist routes and ecological trails in the protected zone will raise the tourist rating of the mentioned settlements. The indisputable value of Roztochchia is hiking, cycling, and horse riding routes, at any time. In general, there are hundreds of kilometers of tourist routes on the Ukrainian-Polish border: dozens of educational trails, tourist trails, and cycling routes. Therefore, the Reserve is also important for the development of international tourism. A mutual visit to the biosphere reserve will contribute to cultural rapprochement and spiritual enrichment of the populations of the two states. This is the important cultural and eco-human significance of the Roztochchia transboundary biosphere reserve. It has been established that several international projects contribute to the development of tourism within the «Roztochchia» TBR, in particular, as part of the Cross-Border Cooperation Program of the European Neighborhood Instrument «Poland-Belarus-Ukraine 2014-2020», the Department of Ecology and Natural Resources implemented the following project together with Polish and Ukrainian partners: «RoweLove Roztochchya - together regardless of borders.» Bicycle races along the «Central Bicycle Route from Krasnik to Lviv» are regularly organized, bringing together hundreds of Ukrainian and Polish cyclists. Therefore, tourism is actively developing within the boundaries of the Transboundary Biosphere Reserve «Roztochchia», although the main task of the biosphere reserve is the preservation of biological diversity, biological resoures, and their sustainable use, the central element in the development and activity of tourism in the TBR is the availability and development of tourist routes, laying and marking of bicycle routes and ecological trails, which will also contribute to the formation of significant socio-economic and ecological advantages in Roztochchia, in general.